Sulfoxaflor induces immunotoxicity in zebrafish (Danio rerio) by activating TLR4/NF-κB signaling pathway - Wang, Kexin; Huang, Yong; Cheng, Bo; Guo, Jing; Peng, Yuyang; Zeng, Suwen; Zhang, June; Lu, Huiqiang (Fish & shellfish immunology, 2023)
Sulfoxaflor is an insecticide that is widely used and affects the nervous system of sucking pests. However, studies on the molecular mechanism of the toxicity of sulfoxaflor to non-target species are limited. Zebrafish (Danio rerio) was used as an experimental subject in this study. Zebrafish embryos were exposed to 20, 25, and 30 mg/L sulfoxaflor solution to detect hatchability, mortality, heart rate, neutrophil count, oxidative stress, and expression of genes related to apoptosis and immune inflammation. The results showed that zebrafish embryos exposed to sulfoxaflor solution increased mortality and growth retardation, and the number of innate immune cells decreased significantly. In addition, the expression levels of apoptotic and proapoptotic genes increased significantly, and oxidative stress-related indexes changed significantly. Toll-like receptor 4 (TLR4)/nuclear factor kappa B (NF-κB) signaling pathway was further studied, and the interleukin 6 (IL-6), interleukin 1 beta (IL-1β), cyclooxygenase-2 (COX2), tumor necrosis factor-alpha (TNF-α), TLR4, and myeloid differentiation primary response 88 (MYD88) gene expression levels were significantly up-regulated. We used small molecule inhibitor QNZ for the rescue experiment and detected the expression of relevant target proteins in the QNZ signaling pathway. QNZ reduced the expression of TLR4/NF-κB signaling pathway-related protein NF-κB p65 in the cytoplasm and nucleus and rescued the number of innate immune cells. In summary, sulfoxaflor may induce developmental toxicity and immunotoxicity in zebrafish by activating the TLR4/NF-κB signaling pathway, which provides a basis for further studies on the molecular mechanism of sulfoxaflor action in the aquatic ecosystem and the development and utilization of QNZ. [Display omitted] •Sulfoxaflor induced the immune toxicity of zebrafish embryos.•Sulfoxaflor activated the TLR4/NF-κB signaling pathway.•QNZ increased the number of neutrophils and macrophages in zebrafish.•QNZ inhibited the activation of the TLR4/NF-κB signaling pathway.